Delivery of social protection programs to combat COVID-19 in Africa - Duchoslav, Jan; Hirvonen, Kalle (AKADEMIYA2063, 2021)
The COVID-19 pandemic has prompted governments across the world to introduce unprecedented lockdowns and other restrictions on mobility to slow the spread of coronavirus and to avoid overwhelming healthcare systems. While often necessary, these measures have led to well-documented disruptions in economic activity (World Bank 2020e). Consequently, many experts and international organizations have raised serious concerns about increased poverty and threats to food and nutrition security (Headey and Ruel 2020; Laborde et al. 2020; Laborde, Martin, and Vos 2020; Torero 2020). In April 2020, the World Food Programme warned that the number of acutely food insecure people in the world could double by the end of 2020 without concerted action (WFP 2020).